2016
DOI: 10.1002/uog.15795
|View full text |Cite
|
Sign up to set email alerts
|

Intrathymic and other anomalous courses of the left brachiocephalic vein in the fetus

Abstract: An intrathymic LBCV is a common condition and appears to be a normal variant in the fetus. The prevalence of a LSVC in our screening population was similar to that reported in previous studies. Anomalous courses of the LBCV are seen occasionally in cases with cardiac malformation. Copyright © 2015 ISUOG. Published by John Wiley & Sons Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
35
1
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 21 publications
4
35
1
2
Order By: Relevance
“…In contrast to previous cases, the present case did not involve any intracardiac anomaly, and the anomalous course of the LBCV was lower at the level of, and posterior to, the descending aorta, which is the convergence point of the aortic and ductal arches. As demonstrated in the present case, the right aortic arch, left‐sided ductus arteriosus, ALSCA and retroesophageal LBCV can be observed easily on 3D/4D color Doppler with HDlive mode, facilitating understanding of the spatial relationships within these variants.…”
contrasting
confidence: 96%
See 2 more Smart Citations
“…In contrast to previous cases, the present case did not involve any intracardiac anomaly, and the anomalous course of the LBCV was lower at the level of, and posterior to, the descending aorta, which is the convergence point of the aortic and ductal arches. As demonstrated in the present case, the right aortic arch, left‐sided ductus arteriosus, ALSCA and retroesophageal LBCV can be observed easily on 3D/4D color Doppler with HDlive mode, facilitating understanding of the spatial relationships within these variants.…”
contrasting
confidence: 96%
“…Retroesophageal or retrotracheal left brachiocephalic vein (LBCV) is a rare anomaly of the LBCV. Other more common anomalous courses of the LBCV include subaortic, retroaortic and intrathymic courses. Since its initial description by Yigit et al ,.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…La incidencia se estima, aproximadamente, en 0.3-0.5% de la población general; el grupo de alto riesgo es de 0.9%, aproximadamente, 3 y en 3-10% de pacientes con cardiopatías congénitas. 1,8 Nuestra incidencia en población de bajo riesgo es menor que la reportada previamente (0.15%).…”
Section: Discussionunclassified
“…That could consequently lead to a displacement of the right SVC toward the right side of the thorax, and therefore more tissue of the mediastinum is present between the right SVC and the aorta. In fact, Karl et al, evaluating the course of the left brachiocephalic vein in over one thousand fetuses, reported that the absence of the left brachiocephalic vein in association with a persistent left SVC was found in one in 350 pregnancies . Furthermore, venous return from the upper left head and neck through the persistent left SVC drains into the coronary sinus and eventually into the right atrium.…”
Section: Discussionmentioning
confidence: 99%